Regional Competitiveness for Achieving Sustainable Development – The Case of Serbia - Nikolic, Miroljub; Filipovic, Milorad; Pokrajac, Slobodan (Industrija, 2016)
Regional competitiveness is without doubt one of the most important component for achieving sustainability of development at local level. Capability of some region to attract investments, especially foreign, and to provide additional employment, export results and innovativeness is something that should be in the focus of development policy. On the other hand, there are different opinions about relations between macro and regional competitiveness and how to measure regional competitiveness at all. In this paper we analyze issues of regional competitiveness of regions in Republic of Serbia measured in 2008 and 2014. Differences in the position of some regions are substantial, but good performances in production, employment, income and export are not translated to better standard of living in analyzed regions. Improved position in ranking of regions does not automatically mean better life and innovativeness as ultimate goals of regional policy.